Causes and consequences of limitations in visual working memory. Issue 1 (15th January 2016) - Fallon, Sean James; Zokaei, Nahid; Husain, Masud
Abstract : Recent methodological and conceptual advances have led to a fundamental reappraisal of the nature of visual working memory (WM). A large corpus of evidence now suggests that there might not be a hard limit on the number of items that can be stored. Instead, WM may be better captured by a highly limited––but flexible––resource model. More resource can be allocated to prioritized items but, crucially, at a cost of reduced recall precision for other stored items. Expectations may modulate resource distribution, for example, through neural oscillations in the alpha band increasing inhibition of irrelevant cortical regions. Our understanding of the neural architecture of WM is also undergoing radical revision. Whereas the prefrontal cortex has previously dominated research endeavors, other cortical regions, such as early visual areas, are now considered to make an essential contribution, for example holding one or more items in a privileged state or "focus of attention" within WM. By contrast, the striatum is increasingly viewed as crucial in determining why and how items are gated into memory, while the hippocampus, it has controversially been argued, might be critical in the formation of temporally resilient conjunctions across features of stored items in WM.